Meta-analysis of the efficacy and safety of cinacalcet combined with active vitamin D in the treatment of secondary hyperparathyroidism in dialysis patients with end-stage renal disease - DAI Chao-run; SHI Yong-jun; CAO Shi-rong (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of cinacalcet combined with active vitamin D in the treatment of secondary hyperparathyroidism(SHPT)in hemodialysis patients with end stage renal disease(ESRD).Methods The Pubmed,Embase and Cochrane Library clinical controlled trials database were searched.All the randomized controlled trials of cinacalcet combined with active vitamin D in the treatment of SHPT in ESRD dialysis patients were collected.The search time was from the database establishment date to December 31,2018.A meta-analysis was performed using RevMan 5.3 software.Results A total of 8 randomized controlled trials were included,including 2 169 patients.Meta-analysis showed that cinacalcet combined with active vitamin D treatment significantly reduced plasma parathyroid hormone in dialysis patients compared with active vitamin D alone [RR=4.66,95% CI(2.27,9.55),P<0.01],blood calcium concentration [MD=-0.81,95% CI(-0.92,-0.69),P<0.01],blood phosphorus concentration [MD=-0.46,95% CI(-0.65,-0.26),P<0.01],and calcium-phosphorus product [MD=-9.86,95% CI(-12.54,-7.19),P<0.01].However,cinacalcet combined with active vitamin D had no significant effects on the incidence of adverse reactions [RR=1.21,95% CI(0.82,1.77),P=0.33] and all-cause mortality [RR=0.90,95% CI(0.54,1.48),P=0.67].Conclusions Cinacalcet combined with active vitamin D for the treatment of ESRD in dialysis patients with SHPT is superior to active vitamin D alone,and does not increase the incidence of adverse reactions,but does not reduce the all-cause mortality.